Impact of low and high partial pressure of carbon dioxide on neuron-specific enolase derived from serum and cerebrospinal fluid in patients who underwent targeted temperature management after out-of-hospital cardiac arrest: A retrospective study - Kang, Changshin; In, Yong Nam; Park, Jung Soo; You, Yeonho; Min, Jin Hong; Yoo, Insool; Cho, Yong Chul; Jeong, Wonjoon; Ahn, Hong Joon; Ryu, Seung; Lee, Jinwoong; Kim, Seung Whan; et al. (Resuscitation, 2020)
In a previous study, low and high-normal arterial carbon dioxide tension (PaCO2) were not associated with serum neuron-specific enolase (NSE) in cardiac arrest survivors. We assessed the effect of PaCO2 on NSE in cerebrospinal fluid (CSF) and serum. This was a retrospective study. PaCO2 for the first 24 h was analysed in four means, qualitative exposure state (qES), time-weighted average (TWA), median, and minimum–maximum (Min–Max). These subgroups were divided into low (LCO2) and high PaCO2 (HCO2) groups defined as PaCO2 ≤ 35.3 and PaCO2 > 43.5 mmHg, respectively. NSE was measured at 24, 48, and 72 h (sNSE24,48,72 and cNSE24,48,72) from return of spontaneous circulation (ROSC). The primary outcome was the association between PaCO2 and the NSE measured at 24 h after ROSC. Forty-two subjects (male, 33; 78.6%) were included in total cohort. PaCO2 in TWA subgroup was associated with cNSE24,48,72, while PaCO2 in the other subgroup were only associated with cNSE24. PaCO2 and cNSE in qES subgroup showed good correlation (r = −0.61; p < 0.01), and in TWA, median, and Min–Max subgroup showed moderate correlations (r = −0.57, r = −0.48, and r = −0.60; p < 0.01). Contrastively, sNSE was not associated and correlated with PaCO2 in all analysis. Poor neurological outcome in LCO2 was significantly higher than HCO2 in qES, TWA, and median subgroups (p < 0.01, p < 0.01, and p = 0.02). Association was found between NSE and PaCO2 using CSF, despite including normocapnic ranges; TWA of PaCO2 may be most strongly associated with CSF NSE levels. A prospective, multi-centre study is required to confirm our results.